1992
DOI: 10.1152/jappl.1992.73.5.1838
|View full text |Cite
|
Sign up to set email alerts
|

Leg vasoconstriction during dynamic exercise with reduced cardiac output

Abstract: We evaluated whether a reduction in cardiac output during dynamic exercise results in vasoconstriction of active skeletal muscle vasculature. Nine subjects performed four 8-min bouts of cycling exercise at 71 +/- 12 to 145 +/- 13 W (40-84% maximal oxygen uptake). Exercise was repeated after cardioselective (beta 1) adrenergic blockade (0.2 mg/kg metoprolol iv). Leg blood flow and cardiac output were determined with bolus injections of indocyanine green. Femoral arterial and venous pressures were monitored for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
113
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(120 citation statements)
references
References 0 publications
7
113
0
Order By: Relevance
“…Whether aortic compression by a gravid uterus enhances cerebral blood flow at the expense of lower extremity blood flow remains unknown. Through their experiments on healthy controls Ide et al showed that an impaired ability to increase cardiac output during exercise with a large muscle mass appears to limit blood flow distribution not only to active muscle 15 but also to such a vital organ as the brain, and that this flow restriction was by way of the sympathetic nervous system 16 . During central blood volume depletion, the increase in sympathetic nerve activity shifts the cerebral autoregulation curve to the right 17 and the vasoconstrictor sympathetic nerve activity overrides vasodilatation 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Whether aortic compression by a gravid uterus enhances cerebral blood flow at the expense of lower extremity blood flow remains unknown. Through their experiments on healthy controls Ide et al showed that an impaired ability to increase cardiac output during exercise with a large muscle mass appears to limit blood flow distribution not only to active muscle 15 but also to such a vital organ as the brain, and that this flow restriction was by way of the sympathetic nervous system 16 . During central blood volume depletion, the increase in sympathetic nerve activity shifts the cerebral autoregulation curve to the right 17 and the vasoconstrictor sympathetic nerve activity overrides vasodilatation 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Third, with respect to the limitations of the model used to evoke the metaboreflex, both static and dynamic contractions followed by local circulatory occlusion increase HR, SV, and CO in humans (3,24,32) and in dogs (29), but the effects on the heart appear to be intensity-dependent (7,8,40). However, the local circulatory occlusion used to trap metabolites that activate metaboreflex prevents venous dilation, which is a major component of metaboreflex activation (10,25).…”
Section: Limitationsmentioning
confidence: 99%
“…Fig. 3 compares the percentage changes in heart rate (HR), cardiac output (CO), mean systemic arterial pressure (MAP), systemic vascular conductance (SVC), and blood flow in active muscles (Q am ) computed with the model at four different exercise levels, with analogous data in humans [2]. As it is clear from the figure, the agreement between simulation and in vivo results is satisfactory.…”
Section: Resultsmentioning
confidence: 74%
“…In order to reproduce muscle exercise hyperemia, we assumed that peripheral resistance in the active muscle compartment (R amp ) depends not only on neural influences, but also on local metabolic control mechanisms. The latter comprise the effect of increased oxygen consumption rate and of metabolic production of vasodilator substances [2,12], each described as a function of exercise intensity through a static characteristic and a firstorder low-pass dynamics. Both an increase of O 2 consumption over the basal level and the release of vasodilator substances produce a decrease in R amp .…”
Section: B Control Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation